2010
DOI: 10.1111/j.1600-0765.2009.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of smoking and smoking cessation with oral health status in Japanese men

Abstract: Smoking has a positive association with missing teeth and periodontitis. However, smoking cessation is beneficial for oral health. The odds of having more than eight missing teeth, or of having periodontitis, in those who had never smoked was similar to that of individuals who reported that they had stopped smoking for 11 years or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 35 publications
2
37
0
2
Order By: Relevance
“…Similarly, the mean number of tobacco product units smoked per day was lower among female than among male current smokers (11.1 and 14.7, respectively). Such a discrepancy between men and women is culture dependent and was even more prominent in a study from Japan, which had to exclude women from the analyses due to exceedingly low numbers of current and former smokers [24]. Nevertheless, the findings regarding smoking cessation and clinically assessed tooth loss among 40- to 75-year-old men were similar to ours.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similarly, the mean number of tobacco product units smoked per day was lower among female than among male current smokers (11.1 and 14.7, respectively). Such a discrepancy between men and women is culture dependent and was even more prominent in a study from Japan, which had to exclude women from the analyses due to exceedingly low numbers of current and former smokers [24]. Nevertheless, the findings regarding smoking cessation and clinically assessed tooth loss among 40- to 75-year-old men were similar to ours.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, studies are often limited to male study populations only [14, 15, 24]. Our study, in contrast, incorporated clinically assessed number of teeth with corresponding self-reported value for both men and women.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study found the odds ratios of having more than eight missing teeth was much higher among current smokers compared to males who had never smoked (OR = 1.67) [24]. An Australian '45 and Up' cohort study based on over 100,000 participants also showed that current smokers had significantly higher odds of tooth loss compared with never smokers (OR = 2.51) [25].…”
Section: Discussionmentioning
confidence: 99%
“…1 , 2 In addition, tooth loss affects daily activities such as speaking, smiling, chewing, and tasting. 3 Prevention of tooth loss thus helps maintain good general health and high quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…7 , 1215 In Japan, numerous studies have examined the association between smoking and tooth loss at all ages. 3 , 1620 There have also been several studies on the associations of tooth loss with nutritional status 21 , 22 and educational level. 23 , 24 However, because most of those studies were conducted among elderly populations, there is little information on factors related to tooth loss in middle-aged populations.…”
Section: Introductionmentioning
confidence: 99%